(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To describe patient evaluation of healthcare providers’ communication at Outpatient Ward - Thai Nguyen National Hospital. Methods: This cross-sectional study was conducted from October 2021 to January 2022. A convenience sample of 221 patients was recruited in the study. Data was collected by Communication Assessment Tool. Results: Patients ranked healthcare providers’ communication as “Good”, with the mean score of 4,19 ± 0,37 (out of 5,0). No significant association between age and communication score was found (r = 0,10, p > 0,05). There were no statistical differences in communication scores among groups of gender (t = 0,29, df = 219, p > 0,05), places of residence (t = -0,06, df = 219, p > 0,05), education levels (F = 0,89, df = 2, t > 0,05), doctors’ specialties (F = 2,67, df = 2, t > 0,05), and previous experience with the outpatient ward (t = 0,03, df = 219, p > 0,05). Conclusions: Healthcare providers’ communication still needs improvement. Further studies, whose samples are more representative, and include more factors influencing patients’ evaluations are recommended.